2020
DOI: 10.3389/fmicb.2020.587750
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Production and Antibiotic Resistance: The Two Sides of AbrB1/B2, a Two-Component System of Streptomyces coelicolor

Abstract: Antibiotic resistance currently presents one of the biggest threats to humans. The development and implementation of strategies against the spread of superbugs is a priority for public health. In addition to raising social awareness, approaches such as the discovery of new antibiotic molecules and the elucidation of resistance mechanisms are common measures. Accordingly, the two-component system (TCS) of Streptomyces coelicolor AbrB1/B2, offer amenable ways to study both antibiotic produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 101 publications
0
3
0
2
Order By: Relevance
“…Recent research on TCSs has shown that some are involved in antibiotic resistance such as VanS/R [ 161 ], CsecC/B [ 73 ], and AbrB1/B2 [ 46 ]. This discovery has presented another potential application for this model species, as using the information obtained with their study not only improves the understanding of antibiotic resistance mechanisms in Streptomycetes, but also the highly relevant human pathogens such as S. aureus or E. faecium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research on TCSs has shown that some are involved in antibiotic resistance such as VanS/R [ 161 ], CsecC/B [ 73 ], and AbrB1/B2 [ 46 ]. This discovery has presented another potential application for this model species, as using the information obtained with their study not only improves the understanding of antibiotic resistance mechanisms in Streptomycetes, but also the highly relevant human pathogens such as S. aureus or E. faecium.…”
Section: Discussionmentioning
confidence: 99%
“…This system has been described as a negative regulator of antibiotic production (ACT and RED) and a positive regulator of vancomycin resistance [ 46 ].…”
Section: Two-component Systems Of Streptomyces Coelicolormentioning
confidence: 99%
See 1 more Smart Citation
“…El desarrollo e implementación de estrategias contra la propagación de superbacterias es una prioridad para la salud pública. Además de aumentar la conciencia social sobre el uso indiscriminado de antibióticos, enfoques como el descubrimiento de nuevas moléculas con actividad antimicrobiana y el esclarecimiento de los mecanismos de resistencia son medidas comunes que se deben fortalecer (49) .…”
Section: Actividad De Nanopartículas De Plata Contra Bacterias Resist...unclassified
“…Dado que el interés en su estudio se debe a su posible implicación en la producción de antibióticos se resalta la información del potencial de las proteínas codificadas por los genes vecinos en la producción de metabolitos secundarios. Por ejemplo, cerca de los genes que codifican el sistema SCO2513/14 están localizado los genes que codifican para un supuesto sistema de dos componentes (SCO2517/18) que regula positivamente la producción de undecilprodigiosina (RED) (Li et al, 2004;Hutchings et al, 2004;Sánchez de la Nieta et al, 2020).…”
Section: *Proteínas Hipotéticasunclassified